The Best $m$-Term Trigonometric Approximations of the Classes $L_{β ,p}^Ψ$ in Uniform Metric - Fedorenko, A. S.; Fedorenko, O.S. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We obtain an exact order estimate for the best approximation of the classes $L_{β ,p}^Ψ$ of functions of one variable in the space $L_{∞}$.